2019
DOI: 10.1021/acs.jpclett.9b00453
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility-Mass Spectrometry of Iodine Pentoxide–Iodic Acid Hybrid Cluster Anions in Dry and Humidified Atmospheres

Abstract: Nanometer scale clusters form from vapor phase precursors and can subsequently grow into nanoparticles during atmospheric nucleation events. A particularly interesting set of clusters relevant to nucleation is hybrid iodine pentoxide-iodic acid clusters of the form (I 2 O 5) x (HIO 3) y , as these clusters have been observed in coastal region nucleation events in anomalously high concentrations. To better understand their properties, we have utilized ion mobility-mass spectrometry to probe the structures of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 44 publications
2
40
1
Order By: Relevance
“…Khanniche et al 85 showed that HIO 3 forms stable hydrates with up to two water molecules but did not investigate larger hydrates. It has also been suggested that the iodate dimer (HIO 3 IO 3 − ) is hydrated with up to 5 water molecules at 65% RH 86 . Therefore, we assumed the HIO 3 monomer to be prevalently bound to three water molecules and estimated its volume based on bulk-phase density measurements 87 .…”
Section: Methodsmentioning
confidence: 99%
“…Khanniche et al 85 showed that HIO 3 forms stable hydrates with up to two water molecules but did not investigate larger hydrates. It has also been suggested that the iodate dimer (HIO 3 IO 3 − ) is hydrated with up to 5 water molecules at 65% RH 86 . Therefore, we assumed the HIO 3 monomer to be prevalently bound to three water molecules and estimated its volume based on bulk-phase density measurements 87 .…”
Section: Methodsmentioning
confidence: 99%
“…The development of GO as implemented in ABCluster, has eliminated this obstacle to a large extent, making a series of productive NPF studies possible [32, 96, 167, 172–197] and revealing valuable insights into atmospheric chemistry (see Figure 7 for some examples). ABCluster has been regarded as a standard tool in this field [198–200].…”
Section: Applicationsmentioning
confidence: 99%
“…Example GMs of molecular clusters obtained with ABCluster: [106, 119] (A) (HNO 3 ) 3 (NH 3 ) 3 (H 2 O) 2 [167], (B) (H 2 NSO 3 H)(H 2 SO 4 ) 2 ((CH 3 ) 2 NH) 3 [176], (C) normalI2normalO54IO33normalH2O100.25em[96], (D) (Gly) 2 (H 2 SO 4 )(NH 3 ) 2 [184]…”
Section: Applicationsmentioning
confidence: 99%
“…[48][49][50][51][52][53][54][55][56][57] Another example is that several authors searched the GMs of clusters consisting of atmosphere related molecules like water, ammonia, nitric acid, hydroxymethanesulfonic acid, sulfuric anhydride, and pentoxide−iodic acid. [58][59][60][61][62][63][64][65][66][67][68][69][70] Using GMs of different sizes, atmospheric cluster dynamics equations can be solved 71 and a lot of atmospheric chemical phenomena were successfully explained. [58][59][60][61][62][63][64][65][66][67][68][69][70] ABCluster was also applied in catalysis, 4,[72][73][74] material science, [75][76][77] solution chemistry, [78][79][80] etc.…”
Section: Introductionmentioning
confidence: 99%